Study of the effects of exposure to ionizing irradiation on the materials used for dental restoration - Fernandes, M.; Paula, D.; Santos, A.; Fanaro, L.; Salvador, V; Okida, R.; Biazolla, E. (Medimond S R L, 2002)
A quantitative study was made about the effects caused by ionizing irradiation on materials used for dental restoration (amalgams, compound resins and compomere), aiming to alleviate in bearers of head and neck cancer, the possible harmful effects of radiotherapy perceived when the repaired teething is within the radiation field. Research also encourages further studies for new alternative materials to be used in dental repair of patients submitted to radiotherapy for head and neck cancer. Test samples were submitted to a gamma radiation beam coming from a cobalt-therapy source and analyzed according to the X-ray fluorescence technique, comparing the chemical composition of the samples before and after irradiation. Radiation detectors such as an ionization chamber and a Geiger-Muller were used to measure the rate of residual dose. Gamma spectrometry with Nal detectors was also performed on the same samples. Results showed that there was no significant change in the chemical composition and that at post-irradiation, samples did not exhibit radiation emission, that is to say they had not become radioactive.
Keywords: dental restoration; radiotherapy; cancer